Impact of Caesar Syria Civilian Protection Act on the International Trade Activities - Nedaa Kazem Muhammad Jawad Al-Mawla (Journal of Madenat Alelem University College, 2022)
Caesar Syria Civilian Protection Act is United States legislation passed into law as part of the National Defense Authorization Act. This act imposes sanctions on American and foreign entities, businesses and individuals, who conduct business activities with industries related to the Syrian regime. It aims to prevent support including infrastructure, military maintenance and energy production to the Syrian government while mitigating potential harm on the civilians. However, the implementation of this acts could severely penalize crucial humanitarian assistance and raises a legal challenge. In particular, this act has direct consequences on the international commercial law and the related modern commercial transactions such as digital currency and jurisdictional borders, which have not been supported by the conventional legislation. Therefore, due to the gap between the conventional and modern legislations, which has highlighted legal issues such as the global imbalances and monopolism, this research work discusses the legal bases of Caesar Syria Civilian Protection Act outside the United State. In addition, it investigates impacts of this act on the international commercial transactions.